Complex Profile of Altered Heavy Metals Accumulation in Multiple Sclerosis, a Relationship with Copper and Zinc Homeostasis - Mohamed, Samar Ramadan; Fadl, Hend A.; Tork, Islam; Omar, Tarek; El-Barrany, Usama; Elshatory, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Multiple sclerosis (MS) is a demyelinating inflammatory disease of the central nervous system white matter. Both of environmental and genetic factors have been implicated in its pathogenesis. Heavy metals generate free radicals causing alteration in genetic material and blood-brain barrier damage. In addition, intracellular accumulation of certain heavy metals can trigger autoimmune reaction against myelin proteins and nerves cytoskeletal proteins. AIM: We aimed to analyse complex profile of altered heavy metals accumulation in multiple sclerosis and relationship with copper and zinc homeostasis. METHODS: The present study was carried out in the period between September 2019 and May 2021 on 86 MS Egyptian patients and 86 age and gender matched healthy controls. Whole blood levels of lead (Pb), mercury (Hg), and Cadmium (Cd) in microgram/liter (μg/L) in addition to Zinc (Zn) and Copper (Cu) in milligram/liter (mg/L) were quantitated using the Agilent ICP-MS-MS. The current study also discussed physiological-toxic metals interactions in these patients. RESULTS: We demonstrated significant relations between toxic heavy metals levels and MS suggested by significantly higher levels of Pb, Hg, and Cd and significantly lower levels of Zn and Cu as well as Cu/ Zn in MS patients than controls. Besides, it could be assumed that; physiological heavy metals homeostasis limits the accumulation of toxic heavy metals that share absorption and transport binding sites, suggested by the significant negative correlations between whole blood levels of Cu and both of Hg and Pb. CONCLUSION: A complex profile of altered elements rather than a single element imbalance in MS pathogenesis is suggested.